Between grammar and conversation : On the well-formedness of beat clashes in natural conversation - Uhmann, Susanne (Cahiers du Centre de Linguistique et des Sciences du Langage, 2022)
This paper deals with the interplay between grammar and conversation. This will be exemplified by a rhythmical phenomenon that has been described as beat clash in metrical phonology. In metrical phonology beat clashes are regarded as highly marked or even deviant rhythmical structures because the phonologically unmarked alternation between prominent and non-prominent syllables is cancelled in favour of a succession of prominent syllables. It will be shown that participants in natural conversation not only let beat clashes happen, but that beat clashes are actively constructed by turning non-prominent syllables into prominent ones. But these achieved beat clashes seem to be restrained by sequential and grammatical constraints: they occur in extended first assessments like stories, news or informings and in seconds to these conversation objects, but they are absent in first and in second assessments of assessment pairs; they respect the prominence structure which is the result of grammatical rules.